2015
DOI: 10.4236/fns.2015.614130
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Flour Improves Fatty Acid Profile and Decreases Hepatic Triglyceride Deposition in Rats Fed with Normocaloric and Hypercaloric Diet

Abstract: This study investigated the effects of replacing casein with soy flour on the fatty acids profile and triglycerides metabolism in the liver of rats that were previously fed with normocaloric and hypercaloric diets based on casein. Wistar male rats were used; one group was fed with control diet (AIN-93) and another with hypercaloric diet (AIN-93 with 34.15% sucrose, 42% fat calories) for 9 weeks. Each group was then divided into two subgroups and casein was replaced with soybean in one of them, obtaining CC (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Treating NAFLD rats with a soybean diet containing coconut oil, magnesium and their combination improved lipid profile, as compared to the positive control groups. In this respect (Razzeto et al, 2015) suggest that replacement of soybean flour instead of casein in normocaloric and hypercaloric diets decreased triglycerides and improved fatty acids profile in liver of rats. The results coincided with that reported by Ascencio et al (2004) whom suggested that hepatic triglycerides were decreased by feeding on soy protein or elevated-fat diets that contain soy protein in contrast to rats fed casein or elevated-fat diets that contain casein.…”
Section: Effect Of Soybean Diet Coconut Oil and High Level Of Magnesium On Serum Lipoprotein-cholesterol Of Rats Suffering From Non-alcohmentioning
confidence: 91%
“…Treating NAFLD rats with a soybean diet containing coconut oil, magnesium and their combination improved lipid profile, as compared to the positive control groups. In this respect (Razzeto et al, 2015) suggest that replacement of soybean flour instead of casein in normocaloric and hypercaloric diets decreased triglycerides and improved fatty acids profile in liver of rats. The results coincided with that reported by Ascencio et al (2004) whom suggested that hepatic triglycerides were decreased by feeding on soy protein or elevated-fat diets that contain soy protein in contrast to rats fed casein or elevated-fat diets that contain casein.…”
Section: Effect Of Soybean Diet Coconut Oil and High Level Of Magnesium On Serum Lipoprotein-cholesterol Of Rats Suffering From Non-alcohmentioning
confidence: 91%
“…Hepatic lipid metabolism is partially controlled by transcription factors: sterol regulatory element binding proteins (SREBPs) and peroxisome proliferator-activated receptors (PPARs) [38]. Soybean intake decreases the expression of SREBP-1c and increases the expression of SREBP-2.…”
Section: Soy Enhances Lipid Profilesmentioning
confidence: 99%
“…In contrast, PPARα regulates genes involved in hepatic fatty acid oxidation. For example, carnitine palmitoyltransferase-1 (CPT-1) is an enzyme that regulates fatty acid β-oxidation [37,38]. In conclusion, SREBP is associated with the regulation of hepatic lipogenesis and reduction of cholesterol synthesis [39].…”
Section: Soy Enhances Lipid Profilesmentioning
confidence: 99%
See 1 more Smart Citation